Pengaruh Pengetahuan Akuntansi dan Pengalaman Usaha terhadap Penggunaan Informasi Akuntansi pada Pelaku UMKM Mitra Mandiri - Fajar Nur Iman; Hilda Kumala Wulandari (Journal of Student Research, 2023)
In Indonesia it has been proven that MSMEs make an important contribution to the economy, such as creating jobs, increasing GDP, increasing export value, and increasing domestic investment. However, business actors still face various challenges, one of which is the problem of using accounting information. The problem involves accounting knowledge and business experience. This study is intended to determine and analyze the impact of accounting knowledge and business experience on the use of accounting information. This study involved a population of 110 Mitra Mandiri MSMEs, with 52 respondents taken as a sample using an accidental sampling technique. Quantitative approach is used in this research. Testing the hypothesis using IBM SPSS Statistics 20. Testing the research data using the validity test, reliability test, classic assumption test, and hypothesis testing. This study shows the results that accounting knowledge partially has a significant effect on the use of accounting information, as well as business experience which also partially has a significant effect on the use of accounting information. In addition, accounting knowledge and business experience simultaneously also have a significant effect on the use of accounting information.